Abstracts of the 22nd Annual Academic Sessions of the College of Community Physicians of Sri Lanka - Shamini Prathapan; Carukshi Arambepola (College of Community Physicians of Sri Lanka, 2017)
All Abstracts of the 22nd Annual Academic Sessions of the College of Community Physicians of Sri Lanka, September 2017 Contains: List of oral presentations List of poster presentations Abstracts of oral presentations Abstracts of poster presentations